Insights into the Evolution of Philanthropy: A Systematic Literature Review - Purwatiningsih, Aris purwatiningsih; Purnamasari, S.; Setyawati, Harini; Indriani, Astiwi; Prawitasari, Dian; Fitria, Shoimatul (Journal of Ecohumanism, 2024)
The article "Insights into the Evolution of Philanthropy: A Systematic Literature Review" explores the development of philanthropy through a systematic review of existing literature. This study identifies key trends, concepts, and approaches that have shaped philanthropic practices, which have evolved from traditional charity into more integrated strategies, such as Corporate Social Responsibility (CSR) and social entrepreneurship. The article also highlights the importance of cross-sector collaboration and the role of technology in expanding the impact of philanthropy. These findings underscore the urgent need for further research on the adaptation of philanthropy to current global challenges.